IMPLEMENTATION OF LECTURER PERFORMANCE: THROUGH CAREER PATHS AND WORK ENVIRONMENT ON PRIVATE LECTURERS IN MEDAN CITY - Henry Aspan; Rozaini; Ari Prabowo; Dian Mahardi Lestari (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
Lecturer performance is not only limited to teaching activities, but also includes research, scientific publications, and community service. According to government regulations, lecturers are expected to be able to make significant contributions in these three aspects to fulfill the Tri Dharma of Higher Education. The purpose of this study was to determine and analyze the partial and simultaneous influence of career path and work environment variables on private lecturer performance in Medan City. The analysis used is associative analysis, this research method is quantitative. The population in this study were all lecturers at 23 private universities in Medan City. The sampling method used the probability sampling method with the simple random sampling technique. So the sample in the study was directly determined to be 120 private lecturers in Medan City. The results obtained from this study indicate that: 1) Career path partially has a significant effect on private lecturer performance in Medan City, 2) Work environment partially has a significant effect on private lecturer performance in Medan City. 3) Career path and work environment simultaneously have a significant effect on private lecturer performance in Medan City. The adjusted R square value of 0.744 can be called the coefficient of determination, this means that 0.744 (74.4%) of lecturer performance can be obtained and explained by career path and work environment while the remaining 25.6% (100% - 74.4% = 25.6%) is explained by variables outside the model that are not studied.